Stress, Anxiety and Depression in Survivors of COVID-19 - Istifarani, Zikrina; Maharatih, Gusti Ayu (Faculty of Medicine Universitas Sebelas Maret, 2022)
Introduction : Stress, anxiety and depression are the most common psychiatric disorders associated with patients infected wilth COVlD-19. The aim of this study was identify descriptions of differences in stress, anxiety and depression in survivors of COVlD-19 compared to non-survivors of COVID-19 and analyze the risk factors that most influence these events.Method: This research is a descriptive analytic study with a cross sectional design. The population are survivors and non-survivors of COVlD-19 who followed the ketofastosis diet and joined the isoman group on the telegram application. The research subjects were COVlD-19 survivors and non-COVlD-19 survivors with a total of 379 subjects. Data collection from online questionnaire containing personal data and DASS 21, and then will be analyzed using Chi Square and logistic regression.Results: The subjects of COVlD-19 survivors experienced anxiety 6,8%, depression 5,5%,and stress 1,6%. The subject of non survivor of COVlD-19 experienced anxiety 4,5%,depression 2,9%, and stress 1,3%. In the Chi Square analysis between stress, anxiety and depression compared to survivors of COVlD-19 and non-survivors of COVlD-19 were p =0.947, p = 0.335, p = 0.153. While the logistic regression analysis test results for risk factors from stress in COVlD-19 survivor were gender (OR=1.520) and having a chronic disease (OR=1.334), for anxiety were gender (OR= 1.743) and having a chronic disease (OR=1.641), then for depression with risk factors also for having chronic disease (OR=1.454) and gender (OR= 0.940).Conclusion: There were no significant differences in stress, anxiety and depression in survivors of COVlD-19 compared to non-survivors of COVlD-19. The most influential risk factor for stress and anxiety in COVlD-19 survivors is gender while for depression is having a chronic disease.